2009
DOI: 10.3748/wjg.15.3744
|View full text |Cite
|
Sign up to set email alerts
|

Transition of children with inflammatory bowel disease: Big task, little evidence

Abstract: Children with chronic long-term disorders need to move to the adult practice at some point in their life. Establishing a smooth and efficient transition process is a complicated task. Transition of medical care to adult practice is defined as the purposeful planned movement of adolescents and young adults with chronic physical and medical conditions from child-centered to adultoriented health care systems. This step is of the utmost importance for several reasons. There is an obvious deficiency of research in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 22 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…Hence, a recent review suggested that the introduction of transition care in IBD patients is a difficult task with limited evidence [12]. However, there is broad consensus from professional surveys, including our own large survey of adult and pediatric gastroenterologists [6], in transition care as an essential requirement in this group of patients.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, a recent review suggested that the introduction of transition care in IBD patients is a difficult task with limited evidence [12]. However, there is broad consensus from professional surveys, including our own large survey of adult and pediatric gastroenterologists [6], in transition care as an essential requirement in this group of patients.…”
Section: Discussionmentioning
confidence: 97%
“…The published guidance for specific models of transition lacks a strong evidence base and originates from expert opinion as a result of weak studies involving small patient numbers, bias and multiple methodological flaws within the data sets. 32 44 46 47 …”
Section: Models Of Ayp Transitionmentioning
confidence: 99%
“…1519 Yet, evidence-based recommendations for IBD transition are lacking. 3,5,7,8 Research that provides an in-depth understanding of how each stakeholder contributes to and defines outcomes of transition for AYAs with IBD is a necessary step to establishing evidence-based recommendations.…”
Section: Introductionmentioning
confidence: 99%